2023
DOI: 10.1088/1757-899x/1287/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of long-term storage of space materials for future constellation missions: study of Braycote® 601 EF lubricant

Abstract: The long-term storage (LTS) of space materials is becoming more and more critical for the next missions. For instance, for MTG (Meteosat Third Generation) mission, 5-year assemble, integration and testing (AIT) time on ground, up to 17.5-year storage for recurring models plus at least 8.5 years in orbit operation are planned. Hence, a good understanding of materials’ aging properties is desirable to ensure that materials’ specifications are still suitable after LTS, and, eventually, to anticipate the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Real-time data for LTS are hardly available, and predictions based upon accelerated models typically lack verification. The retainment of tribological properties of the PFPE-based grease Braycote 601 EF (Castrol) after 17 years of storage was presented in a NASA study, and the findings were confirmed in a recent publication [23,24].…”
Section: Introductionmentioning
confidence: 65%
“…Real-time data for LTS are hardly available, and predictions based upon accelerated models typically lack verification. The retainment of tribological properties of the PFPE-based grease Braycote 601 EF (Castrol) after 17 years of storage was presented in a NASA study, and the findings were confirmed in a recent publication [23,24].…”
Section: Introductionmentioning
confidence: 65%